SCHISTOSOMIASIS: EPIDEMIOLOGICAL ANALYSIS IN THE FIVE REGIONS OF BRAZIL - Azevedo, Raquel da Silva Machado; Gomes, Keyla Nunes Farias; Rocha, Leandro; Faria, Robson Xavier (Seven Editora, 2024)
Schistosomiasis is a parasitic disease caused by the helminth Schistosoma mansoni, which affects approximately 240 million people globally, with Brazil being the most affected country in the Americas, with 1.5 million infected people. The prevalence of this disease is associated with unfavorable socioeconomic conditions and poor basic sanitation. This study aimed to evaluate the epidemiological profile of cases of S. mansoni infection in five regions of Brazil (Northeast, North, South, Southeast and Central-West) between 2010 and 2021. Data from the Schistosomiasis Control Program Information System (PCE) and the Notifiable Diseases Information System (SINAN) were used to analyze variables such as sex, age group, race and incidence by region. The results revealed that schistosomiasis is more common in Northeast, where the combination of unfavorable economic conditions and the presence of snails of the genus Biomphalaria contribute to its spread. In contrast, South and parts of Southeast a lower incidence, which was attributed to better sanitary conditions. The infection predominantly affects men, especially those involved in activities in contact with potentially contaminated aquatic environments, such as fishing and agriculture, who seek medical care less frequently. The most affected age group varies in North, between 40 and 59 years old, and in Northeast, this age group stands out between 2015 and 2021. These data highlight socioeconomic inequalities in the prevalence of the disease, with a higher incidence among people of mixed race in North, Northeast, Southeast and Central-West in South the prevalence is higher among whites. The persistence of schistosomiasis in Brazil highlights the need for control strategies according to the regional epidemiological profile. Schistosomiasis continues to be an important public health problem in Brazil, requiring strategies that prioritize basic sanitation, health education, treatment and epidemiological surveillance to reduce transmission and improve the quality of life of affected populations. DOI:https://doi.org/10.56238/sevened2024.037-046